Prescription pattern and prevalence of potentially inappropriate medications among elderly patients in a Nigerian rural tertiary hospital - Fadare JO; Agboola SM; Opeke OA; Alabi RA (Dove Medical Press, 2013)
Joseph O Fadare,1 Segun Matthew Agboola,2 Olumide Augustine Opeke,3 Rachel A Alabi41Department of Medical Pharmacology and Therapeutics, Obafemi Awolowo University, Ile-Ife, Nigeria; 2Department of Family Medicine, 3Department of Internal Medicine, 4Pharmacy Department, Federal Medical Centre, Ido-Ekiti, NigeriaIntroduction: Polypharmacy and inappropriate prescriptions are prominent prescribing issues with elderly patients. Beers criteria and other guidelines have been developed to assist in the reduction of potentially inappropriate medications prescribed to elderly patients. The objectives of this study were to assess the prescribing pattern for elderly Nigerian outpatients and estimate the prevalence of potentially inappropriate medications among them using the Beers criteria.Methodology: This was a prospective cross-sectional study of elderly patients (65 years and above) who were attending the general outpatients clinic of a rural Nigerian hospital. For the drug utilization aspect of the study, drug-use indicators were assessed using established World Health Organization guidelines, while the Beers criteria was used to screen for potentially inappropriate medications.Result: The medical records of 220 patients aged 65 years and above were utilized for the study. A total of 837 drugs were prescribed for the patients, giving an average of 3.8 ± 1.3 drugs per person. Antihypertensive drugs accounted for 30.6% of the prescriptions, followed by multivitamins/food supplements (11.5%) and analgesics (10.8%). A review of the prescribed medications using the 2012 Updated Beers Criteria by the American Geriatric Society identified 56 patients with at least one potentially inappropriate medication prescribed giving a rate of 25.5%. The drug groups identified were nonsteroidal anti-inflammatory drugs, antihistamines, and amitriptyline.Conclusion: Polypharmacy and prescription of potentially inappropriate medications are major therapeutic issues in Nigeria. There is a need for prescriber training and retraining with emphasis on the geriatric population.Keywords: drug utilization pattern, elderly patients, rational use of medicines, adverse drug reactions, Beers criteria